2005
DOI: 10.1111/j.1349-7006.2005.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination of HSP105 leads to tumor rejection of colorectal cancer and melanoma in mice through activation of both CD4+ T cells and CD8+ T cells

Abstract: We report that HSP105, identified by serological identification of antigens by recombinant expression cloning (SEREX), is overexpressed in a variety of human cancers, including colorectal, pancreatic, thyroid, esophageal, and breast carcinoma, but is not expressed in normal tissues except for the testis. The amino acid sequences and expression patterns of HSP105 are very similar in humans and mice. In this study, we set up a preclinical study to investigate the usefulness of a DNA vaccine producing mouse HSP10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…The activation of tumor-specific CD4 + and CD8 + T cells has been shown to result in tumor rejection in a mouse colorectal cancer model (38,41). Collectively, these findings suggest the lymphocytes form part of a tumor-specific host response involved in minimizing the spread of cells from the primary tumor.…”
Section: Discussionmentioning
confidence: 74%
“…The activation of tumor-specific CD4 + and CD8 + T cells has been shown to result in tumor rejection in a mouse colorectal cancer model (38,41). Collectively, these findings suggest the lymphocytes form part of a tumor-specific host response involved in minimizing the spread of cells from the primary tumor.…”
Section: Discussionmentioning
confidence: 74%
“…Hsp110 itself could also serve as a potential tumor antigen since it is often overexpressed in various cancers and correlates with the stage of diseases (131133). Indeed, an Hsp110 DNA vaccine inhibits both CT26 colorectal cancer and B16 melanoma in mice, accompanied with activation of Hsp110-specific CD4 + and CD8 + T cells (134). It should be noted that in our studies mice treated with recombinant Hsp110 chaperone complex vaccine only develop a robust immune response against associated protein antigen, not Hsp110 itself (99).…”
Section: Modulation Of Tumor Immunogenicity By Hsp110 and Grp170mentioning
confidence: 99%
“…HSP105 in normal adult mice is expressed in only certain tissues, and expression in these tissues is less than that in C26 tumor cells, suggesting a low risk of damage to normal tissues posed by HSP105 antigen-induced immune responses (6). To investigate whether immunization of the mice with HSP105-derived peptides causes autoimmunity, HLA-A2 Tgm were immunized with the HSP105 A2-7 and A2-12 peptides emulsified in incomplete Freund’s adjuvant at 7-day intervals and then sacrificed 7 days after the second vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Using immunohistochemical analysis, we previously found that HSP105 was specifically overexpressed in 44 of 53 (83.0%) colorectal cancer patients (4). It has also been reported that DNA vaccination with both HSP105 and bone marrow-derived dendritic cells (BM-DCs) pulsed with HSP105 led to tumor rejection of colorectal cancer but did not induce an autoimmune reaction in mice (68). …”
Section: Introductionmentioning
confidence: 99%